THU0186 SAFETY, TOLERABILITY AND PHARMACOKINETICS OF MBS2320, A SELECTIVE MODULATOR OF IMMUNE METABOLISM, IN HEALTHY VOLUNTEERS AND PATIENTS WITH RHEUMATOID ARTHRITIS. (June 2019) - Patel, Lisa; Marcus, Paul; Bush, Jim; Gray, Andy; Fitzgerald, Richard; Abraham, Sonya; Foster, Martyn; Huatan, Hiep; Skillern, Laurence; Daroszewska, Anna; Hof, Rob Van't; Williams, Sam
Abstract : Background: Despite the availability of several treatment options some patients with Rheumatoid Arthritis (RA) fail to benefit and for those who do response rates are similar across therapeutic classes. Thus there remains a need for new therapies with novel mechanisms of action. MBS2320 is a selective modulator of immune metabolism that shows anatomically appropriate osteoid layering and a broader spectrum of osteoprotective efficacy compared to TNFα inhibition in preclinical models. Objectives: To investigate the safety, tolerability and pharmacokinetics of MBS2320 in healthy volunteers and patients with Rheumatoid Arthritis (RA) receiving a stable dose of methotrexate (MTX). Methods: Cohorts of healthy volunteers (randomised 6:2 drug:placebo) received single or multiple oral doses of MBS2320 for 14 days. Single Ascending Dose (SAD) cohorts comprised 2, 10, 25, 50, 75, 125, 250, 375 mg (PO) and Multiple Ascending Dose (MAD) cohorts 75, 100, 160 mg/d. Patients with RA received 75 mg/d for 14 days in addition to their existing weekly MTX treatment. Safety and tolerability were assessed throughout. Plasma MBS2320 (SAD, MAD and patients with RA) and MTX (patients with RA only) were measured using LC-MS/MS. In patients with RA, C-reactive protein (CRP) and biomarkers of bone turnover were assessed on Day 14. Results: A total of 96 healthy subjects and 9 patients with RA entered the Study and were randomised to the drug or matching placebo. MBS2320 was well tolerated by healthy subjects at single oral doses of 2 to 375 mg. There were no serious adverse events (SAEs). Nausea was the most commonly reported adverse event (AE) and occurred most frequently at the high doses but was mild and resolved without treatment. Daily doses of 75 to 160 mg QD MBS2320 for 14 days were generally well tolerated by healthy subjects. The most common drug-related treatment emergent adverse events (TEAEs) were gastrointestinal disorders, particularly nausea. There were no significant effects on clinical laboratory tests, vital signs, ECG or physical examination. Multiple doses of MBS2320 (75 mg) were also generally well tolerated by subjects with RA when co-administered with MTX. There were no clinically significant findings or trends in the laboratory tests, vital signs or ECG data, and no clinically significant findings on physical examination. No SAEs were reported. The majority of TEAEs were mild in severity with diarrhoea and nausea reported most frequently. In healthy subjects, MBS2320 was steadily absorbed following doses of 50 to 375 mg MBS2320. Systemic exposure (AUC) increased in a dose-proportional manner across all doses and was unaffected by food. In RA patients there was no indication of a PK interaction between MTX and MBS2320 in either direction. In patients with RA, serum CTX-1, P1NP and osteocalcin increased following 14 days of treatment, while TRAP5b was decreased or unchanged. Median CRP was decreased relative to baseline in after 7 days' treatment with MBS2320, and remained low on Day 14. Conclusion: MBS2320 was well tolerated for up to 14 days when administered to healthy volunteers and to patients with RA receiving MTX. Systemic exposure was dose-proportional with no evidence of a pharmacokinetic interaction with MTX. Evaluation of biomarkers of bone turnover and inflammation in RA patients showed changes consistent with those expected of an agent with the potential to directly protect the bone and simultaneously ameliorate inflammation. Louise Jopling, Ian Anderson, Ian Gourley, Helen Marley and Ezi Otti Disclosure of Interests: Lisa Patel Shareholder of: Shareholder of Istesso Ltd, Employee of: Employee of Istesso, Paul Marcus Consultant for: Istesso Ltd, Jim Bush Shareholder of: Labcorp, Employee of: Covance, Andy Gray Shareholder of: Shareholder of Istesso Ltd, Consultant for: Istesso Ltd, Employee of: Astra Zeneca, Richard Fitzgerald: None declared, Sonya Abraham Shareholder of: UCB Pharma, Grant/research support from: Pfizer, Riche, Abbvie, Consultant for: Abbvie Roche Pfizer BMS UCB pharma, Eli Lilly, Employee of: UCB Pharma, Martyn Foster Shareholder of: AstraZeneca, Consultant for: Istesso, Levicept, Employee of: AstraZeneca, Hiep Huatan Consultant for: Istesso Ltd, Employee of: Pfizer, Laurence Skillern Consultant for: Istesso, Employee of: Astellas, Anna Daroszewska Consultant for: Istesso Ltd, Rob van't Hof Shareholder of: OsteoRx Ltd, Sam Williams Shareholder of: Shareholders of Istesso Ltd, Employee of: Employees of Istesso